Digital ecosystems and migration responses to climate extremes: case study from Rahim Yar Khan District, Punjab in Pakistan - Waqar, Kanwal; Hafeez, Mohsin; Rehman, Maryam; Aeman, Hafsa (International Water Management Institute (IWMI). CGIAR Initiative on Fragility, Conflict, and Migration, 2024)
The report titled "Digital Ecosystems and Migration Responses to Climate Extremes in Pakistan" focuses on the impacts of climate change, particularly in Rahim Yar Khan district, Punjab. A digital ecosystem is a network of digital technologies, individuals, and organizations working together to achieve developmental goals like poverty reduction, economic growth, and improved healthcare and disaster management. The study highlights how climate-induced events like floods and droughts have driven migration, affecting vulnerable communities, especially women. As indicated in recent study, approximately 2 million people in Pakistan are expected to become climate migrants by 2050 due to climate disasters. The report emphasizes the need for better disaster preparedness and response mechanisms, including the role of digital ecosystems, social media, and early warning systems in building community resilience. However, there are challenges, such as limited access to technology, the Gender Digital Divide, and inadequate government support for displaced populations.